Characterization of the carrier‐mediated transport of ketoprofen, a nonsteroidal anti‐inflammatory drug, in rabbit corneal epithelium cells. (7th September 2012) - Fujii, Shinobu; Hayashi, Hideki; Itoh, Kunihiko; Yamada, Shizuo; Deguchi, Yoshiharu; Kawazu, Kouichi
Abstract Objectives Using rabbit corneal epithelial cells (RCECs), the transport of a nonsteroidal anti‐inflammatory drug (NSAID) [3H]ketoprofen across the cornea was investigated with the aim of revealing the mechanism of uptake. Methods [3H]Ketoprofen transport was evaluated by measuring the permeability across the RCECs layers. Key findings [3H]Ketoprofen uptake was time, temperature and pH dependent. Maximal uptake occurred from a solution with a pH of 5.25. Uptake was also reduced by metabolic inhibitors (sodium azide and dinitrophenol (DNP)) and proton‐linked monocarboxylate transporter (MCT) inhibitors (carbonyl cyanide p‐trifluoromethoxyphenylhydrazone (FCCP) and α‐cyano‐4‐hydroxycinnamic acid (CHC)). [3H]Ketoprofen uptake was significantly inhibited by various monocarboxylates and other NSAIDs and by MCT and/or organic anion transporter (OAT) inhibitors probenecid and p‐aminohippurate, but was unaffected by organic anion‐transporting polypeptide (OATP) inhibitors bromosulfophthalein and taurocholate. The specific uptake of [3H]ketoprofen was saturable. Eadie–Hofstee plots indicated the involvement of high‐ and low‐affinity components. The Km and Vmax values for the high‐ and low‐affinity components of [3H]ketoprofen uptake were 0.56 and 24 mm, and 0.37 and 61 nmol/min/mg of protein, respectively. Benzoic acid, a substrate and inhibitor of MCTs, selectively inhibited low‐affinity [3H]ketoprofen uptake. Conversely, indometacin inhibited high‐affinity [3H]ketoprofen uptake. Conclusion The results of this study suggest that the monocarboxylate transport system partly accounts for the low‐affinity component of [3H]ketoprofen uptake, and that the carrier‐mediated transport systems such as the OAT family, shared by NSAIDs account for the high‐affinity component.